2021
DOI: 10.1029/2021gl093007
|View full text |Cite
|
Sign up to set email alerts
|

A Morphodynamic Model to Evaluate Long‐Term Sandbar Rebuilding Using Controlled Floods in the Grand Canyon

Abstract: Controlled floods released from dams have become a common restoration strategy in river systems worldwide. Here we present a morphodynamic model of sandbar volume change for a subset of sandbars of the Colorado River in Grand Canyon National Park, where controlled floods are part of a management strategy focused on sandbar maintenance. We simulate sandbars as a triangular wedge, where deposition and erosion are modeled using physically based approaches that are driven by nearly continuous observations of flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Sci. Downloaded from cdnsciencepub.com by 44.224.250.200 on 03/05/23 successful in enhancing beaches and increasing the prevalence of associated low-velocity backwater habitats (Schmidt and Grams 2011;Melis et al 2015;Mueller and Grams 2021). Initially, it was suggested that increases in such habitat would benefit humpback chub; however, studies to date suggest such impacts are small in comparison to other drivers (Dodrill et al 2015;Yackulic et al 2018;Dibble et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sci. Downloaded from cdnsciencepub.com by 44.224.250.200 on 03/05/23 successful in enhancing beaches and increasing the prevalence of associated low-velocity backwater habitats (Schmidt and Grams 2011;Melis et al 2015;Mueller and Grams 2021). Initially, it was suggested that increases in such habitat would benefit humpback chub; however, studies to date suggest such impacts are small in comparison to other drivers (Dodrill et al 2015;Yackulic et al 2018;Dibble et al 2021).…”
Section: Introductionmentioning
confidence: 99%